2021
DOI: 10.1002/nop2.1076
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety, quality of care and missed nursing care at a cardiology department during the COVID‐19 outbreak

Abstract: At the end of 2019, a novel coronavirus resulted in an outbreak of coronavirus disease 2019 (COVID-19), which started in Wuhan, China. In March 2020, the World Health Organization (WHO) characterized COVID-19 as a pandemic (World Health Organization, 2020), and in line with other European countries, several regions in Sweden needed to expand their capacity for treating patients suffering from COVID-19.The literature indicates that nurse staffing has a large impact on whether the required nursing care can be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 51 publications
1
59
0
4
Order By: Relevance
“…In line with the findings of the present study, von Vogelsang et al [ 59 ], who investigated the deficiencies in nursing care during the COVID-19 pandemic at inpatient wards, highlighted the crucial role of lower patients’ admissions and the maintenance of nurse/patient ratio. However, during the first wave of the COVID-19 pandemic, the standards of care at non-COVID wards were regarded to be inadequate [ 60 ]. Even more, the pandemic crisis raised issues of inconsistencies in nursing care and low nursing performance due to nurses’ mental health symptoms [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with the findings of the present study, von Vogelsang et al [ 59 ], who investigated the deficiencies in nursing care during the COVID-19 pandemic at inpatient wards, highlighted the crucial role of lower patients’ admissions and the maintenance of nurse/patient ratio. However, during the first wave of the COVID-19 pandemic, the standards of care at non-COVID wards were regarded to be inadequate [ 60 ]. Even more, the pandemic crisis raised issues of inconsistencies in nursing care and low nursing performance due to nurses’ mental health symptoms [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the abovementioned facts and research outcomes, pandemics can severely impact the healthcare system including the workforce (i.e., nurses) through exposure ( Ives et al, 2009 ; Seale et al, 2009 ). A recent study conducted in Stockholm, Sweden ( Nymark et al, 2021 ) during the first wave of the COVID-19 pandemic revealed more overtime hours and absence from work amongst registered nurses and nurse assistants. Also, patient safety and quality of care were perceived worse among them ( Nymark et al, 2021 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…A recent study conducted in Stockholm, Sweden ( Nymark et al, 2021 ) during the first wave of the COVID-19 pandemic revealed more overtime hours and absence from work amongst registered nurses and nurse assistants. Also, patient safety and quality of care were perceived worse among them ( Nymark et al, 2021 ). This is an example of how nurses and nursing care are susceptible to be negatively influenced during pandemics.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Additionally, the indicators with the most significant negative impact were those of screening, such as the indicator of diabetic foot screening ( 11 ). Then a survey study among registered nurses and nurse assistants at a cardiology department in Sweden reports that the nursing staff in the COVID-19 pandemic perceived the quality of care to be lower than before it started ( 21 ). Overall, 75% of oncology patients from the Netherlands stated in an online survey that the COVID-19 pandemic did not influence their contact with the hospital.…”
Section: Resultsmentioning
confidence: 99%